In Memoriam Professor Wojciech Majewski - DOBRUCKI, Andrzej Bogdan (Archives of Acoustics, 2021)
Professor Wojciech Majewski was a specialist in the field of telecommunication acoustics, dealing particularly with the issues of analysis, synthesis, transmission and recognition of speech and speakers, as well as methods of assessing the quality of speech signal transmission. Particular scientific achievements include comparative research on subjective and objective methods of speaker recognition under conditions of voice masking and imitation of the voice of other speakers, as well as leading participation in the development of an integrated voice recognition method, which was applied in the process of combating crimes committed using the telephone. In 1979, during his visit at the Michigan University, He was the author or co-author of over 100 scientific papers and 4 books. He promoted 11 doctorates in technical sciences.